Tween Girls' Dressing and Young Femininity in Singapore Too Much, Too Young, Too Fast? - Loh, Bernice (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides an insight into girls' cultural identities and young femininities through an understanding of tween girls' dressing in Singapore. The book adopts a girl-centred approach to shed light on the narratives and experiences of young Singaporean girls that have often been overlooked. It draws on the conversations with young Singaporean girls aged 8 to 12 to understand how they wanted to dress, from where they gained their inspiration, and what the social factors were that influenced their dressing. Through understanding how girls want to fashion themselves, the book shows that it is imprecise to discuss issues based on the assumption that there is one dominant, 'correct' way to grow up as a young person in Singapore. This book unpacks how young Singaporean girls negotiate their cultural identities through clothing that do not simply conform to or reflect their roles as students. It also shows how girlhood in Singapore is multi-faceted and the values and meanings that tween girls' attach to their dressing intersect at the personal, social, and cultural level. The book offers new ways of approaching and looking at girls' adult-like dressing that move beyond the discourse of sexualisation. In establishing a space for young Singaporean girls' voices in an area that has been dominated by studies from the West, this book also shows how the focus on tween girls in Asia can contribute to and advance the current state of girls' studies.
Introduction -- Chapter 1: Understanding girls' dressing -- Chapter 2: Girlhood in Singapore -- Chapter 3: YouTube and girls' dressing -- Chapter 4: A cultural perspective of tween girls' dress -- Chapter 5: Girls' interpretive repertoires -- Conclusion.
Keywords: Sociology; Social groups; Youth-Social life and customs; Sex; Ethnology; Sociology of Family, Youth and Aging; Youth Culture; Gender Studies; Sociology of Family, Youth and Aging; Sociocultural Anthropology